Environmental conditions shape the global distribution of ant societies - Eddie Pérochon; Benoit Guénard; Jérôme M. W. Gippet; Tristan Klaftenberger; Sébastien Ollier; Cleo Bertelsmeier (Proceedings of the National Academy of Sciences, 2026)
Sociality has evolved several times and is a key strategy for overcoming environmental challenges and promoting ecological success. Yet, it remains unclear how environmental conditions shape global variation in social traits of animals. With their diverse societies and global distribution, ants are ideal to test whether environmental conditions influence the distribution of animal social traits worldwide. Here, we used trait data for a total of 3,299 ant species to explore how three key social traits (reproductive structure, colony size, and worker polymorphism) vary with environmental conditions globally. We show that trait compositions are strongly structured by biomes, indicating that habitat types, as well as environmental factors like temperature and seasonality, influence sociality. Our findings highlight the crucial role of the environment in shaping the global distribution of sociality in ants, contributing to a better understanding of how complex animal societies evolved.